Islamic and Western ethics in advertising - Mokhtar, Aida (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Ethical advertising and Islamic advertising appear dissimilar as the former refers to Western ethics and the latter Islamic ethics. The question of whether ethical advertising should be used in place of Islamic advertising is raised in the paper. This discussion is significant as selecting an apt concept for advertising to Muslims is essential. This is supported by SapirWhorf hypothesis that claims a person’s conception of the world is dictated by language. When the concept of Islamic advertising is used, Islamic ethics and not Western ethics is brought to the foreground. The article springs a surprise of whether there is indeed the demarcation between Western and Islamic ethics or not. Western categories of normative ethics have been used by Muslim scholars with the difference being the prerequisite for adapting Western ethics using the main sources of Islam in the form of the Qur’an and Sunnah.